Atomic scale investigation of arsenic segregation in high-k metal gate stacks. (1st March 2016) - Estivill, Robert; Juhel, Marc; Gregoire, Magali; Grenier, Adeline; Delaye, Vincent; Blavette, Didier
Abstract: The redistribution of arsenic in high-k metal gate stacks on fully depleted silicon was investigated. Both gates corresponding to n and p-type devices were analysed by atom probe tomography. Reconstruction shows the presence of arsenic at various interfaces. The most important accumulation is between the silicon and titanium nitride. This is confirmed by energy dispersive X-ray spectroscopy. The maximum concentration is in the order of 10%, with a thickness around 1 nm. Interaction energies between dopants and interface have been estimated to be approximately 0.4 eV. The arsenic is shown by X-ray photo-electron spectroscopy to be bonded to silicon throughout. Graphical abstract: